2017
DOI: 10.4067/s0718-95162017005000001
|View full text |Cite
|
Sign up to set email alerts
|

Residue addition frequency influences respiration, microbial biomass and nutrient availability in soil amended with high and low C/N residue

Abstract: In previous studies, we showed that the C/N ratio of the first residue added influences soil respiration, microbial biomass and nutrient availability after the second residue addition which we refer to as legacy effect. The aim of the study was to investigate the effect of residue addition frequency on microbial activity and nutrient availability, and the legacy effect.In Part A, the effect of high C/N residue (H) addition frequency in the first 16 days (d) was studied by adding H to soil once (d0), twice (d0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…They found that compared to a single addition, repeated addition increased cumulative respiration per g C added and that this stimulation increased with addition frequency. In their study, addition frequency did not influence microbial biomass C or available N. Zheng and Marschner (2017b) added high or low C/N residue once (d0), twice (d0, 8) or four times (d0, 4, 8, 12). Cumulative respiration, microbial biomass and nutrient availability compared to single addition were lower on d7 with residue added twice or four times, but higher on d15.…”
Section: Introductionmentioning
confidence: 88%
“…They found that compared to a single addition, repeated addition increased cumulative respiration per g C added and that this stimulation increased with addition frequency. In their study, addition frequency did not influence microbial biomass C or available N. Zheng and Marschner (2017b) added high or low C/N residue once (d0), twice (d0, 8) or four times (d0, 4, 8, 12). Cumulative respiration, microbial biomass and nutrient availability compared to single addition were lower on d7 with residue added twice or four times, but higher on d15.…”
Section: Introductionmentioning
confidence: 88%
“…Soil physical properties such as texture, structure, water holding capacity, pore size distribution, and pore connectivity, however, may have significant effects on decomposition and mineralization (Cai et al 2016;Zhang and Marschner 2018). Differences in the water holding capacity led to variations in microbial activity and carbon and nitrogen mineralization dynamic (Thomsen et al 1999;Zheng and Marschner 2017). Recent studies have investigated carbon and nitrogen mineralization in treated soils with organic matter (Guo et al 2014;Moreno-Cornejo et al 2014;Sun et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Application of organic manures had significant influence on organic carbon depleted arable soils by improving maize productivity and soil physico-chemical properties (Mahmood et al, 2017). Also, residue addition frequency strongly influenced soil respiration, microbial biomass and nutrient availability after addition of low C/N residue, for example, young faba bean (Vicia faba L.) (Zheng and Marschner, 2017).…”
Section: Discussionmentioning
confidence: 99%